Online vocabulary games for teaching and learning arabic - Muhammad Sabri Sahrir,; Ghazali Yusri, (Penerbit UKM, 2012)
Arabic vocabulary learning is in dire need for additional teaching and learning aids, especially with the integration of advanced multimedia application such as digital or online games. This article reports on the findings of a study on the implementation of an online Arabic vocabulary learning games prototype among teenage learners in the Centre for Foundation Studies (CFS), International Islamic University Malaysia (IIUM). The evaluation on the usability, practicality and effectiveness of the game's prototype was conducted by various experts of Instructional Designers and Subject Matter Expert, and the different users among learners and lecturers. The formative evaluation is divided into three main phases: pre-formative evaluation, formative evaluation one and formative evaluation two. Findings from the evaluation process show that the online game enhances learner’s perceived perception, concentration, immersion and knowledge improvement. Positive reports are also gathered from qualitative data from the implementation of open-ended surveys, interview sessions, think-aloud methods, class observations, and testimonials. This study has indicated usability, practicality and effectiveness of online games in its application in Arabic language learning among elementary learners with suggestions and comments for further improvement of the game's prototype. The study indicates that students personally feel that they are able to learn Arabic vocabulary through this online game's application and this data will provide directions for further research.